Arduino based stepper motor speed regulation for robotics applications - Sreejyothi, Khammampati R.; Chenchireddy, Kalagotla; Srujana, Abbagoni; Nagaraju, Dharavath; Ramcharan, Golluri; Raghu, Dhunnapothula (Institute of Advanced Engineering and Science, 2024)
This paper presents a stepper motor drive using the hybrid two-phase model. The stepper motor changes the pulse signals into angular displacement with some angles. Stepper motors are used to control the speed and are also more reliable for smooth operations. The stepper motor provides constant holding torque with controlled speed ranges from 0 to 6000 range. The closed-loop control technique with park transformation is used to control the speed torque variables in a design range. The simulation and hardware results were discussed in MATLABsoftware. The verified simulation results are motor source voltage, motor source current, motor speed, and torque. The hardware results are also implemented in this paper, the implemented circuit by using Arduino microcontroller.